CONTINUITY OF SYMMETRIC FACTORS OF HYPERSPACES OF INCLUSION AND CAPACITIES - Микицей, Оксана Ярославівна; Никифорчин, Олег Ростиславович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Symmetric variants of tensor products of normed regular non-additive measures was constructed, and their continuity has been proved.